Vitamin D Supplementation Modulates T Cell–Mediated Immunity in Humans: Results from a Randomized Control Trial - Konijeti, Gauree Gupta (J Clin Endocrinol Metab, 2016)
CONTEXT: Although studies have linked vitamin D deficiency with immune-mediated diseases, data demonstrating a direct effect on T-cell function are sparse. OBJECTIVE: Our objective was to determine whether oral vitamin D3 influences T-cell activation in humans with vitamin D deficiency. DESIGN: This was a single-center ancillary study within Vitamin D Therapy in Individuals at High Risk of Hypertension, a double-blind, multicenter, randomized controlled trial. SETTING: This study was undertaken in a single academic medical center. PARTICIPANTS: Adults with vitamin D deficiency and untreated pre- or early stage I hypertension were included. INTERVENTION: In Vitamin D Therapy in Individuals at High Risk of Hypertension, participants were randomized to either low- (400 IU daily) or high- (4000 IU daily) dose oral vitamin D3 for 6 months. In this ancillary study of 38 patients, we measured CD4+ T-cell activation estimated by intracellular ATP release after stimulation of whole blood with plant lectin phytohemagglutinin collected at baseline (pretreatment) and 2-month follow-up. MAIN OUTCOME MEASURE: Determining whether ATP level changes were significantly different between treatment groups was the main outcome measure. RESULTS: Treatment with 4000 IU of vitamin D3 decreased intracellular CD4+ ATP release by 95.5 ng/ml (interquartile range, −219.5 to 105.8). In contrast, 400 IU of vitamin D3 decreased intracellular CD4+ ATP release by 0.5 ng/ml (interquartile range, −69.2 to 148.5). In a proportional odds model, high-dose vitamin D3 was more likely than low-dose vitamin D3 to decrease CD4+ ATP release (odds ratio, 3.43; 95% confidence interval, 1.06–1.11). CONCLUSIONS: In this ancillary study of a randomized controlled trial, we found that high-dose vitamin D3 significantly reduced CD4+ T-cell activation compared to low-dose vitamin D3, providing human evidence that vitamin D can influence cell-mediated immunity.